SYNTHESIS FISETIN - FIRMANSYAH (NIM: 20508004), DIKHI
Flavonoid compounds are secondary metabolites which can be found in higher plants. They are the most abundance compounds which are widely distributed in leaf, fruit, flower, nuts, seeds, wood, and root of plants. Now days almost 9000 structure have been characterized. In plant tissue, flavonoids have various function and activity such as, physiological function, biochemistry, and ecological function. As example flavonoids play important roles in UV-protection, flower coloration, interspecies interaction, and plant defence. In this research, fisetin, which is a flavonoid compound, will be synthesized. Fisetin have recently been identified as a neurotrophic factor which could be used for treating central neuron system diseases. Fisetin also has an activity in preventing atherosclerosis which is the primary cause of heart disease and stroke. Because of neurotrophic factor properties, fisetin is potentiall in treating several diseases such as Alzheimer, Parkinson, HIV dementia, and to enhance memory. Fisetin are naturally distributed in fruit, such as strawberry, apple, persimmon, grape, kiwi fruit, and peach. Fisetin are also found in vegetables such as lotus root, onion, tomatoes, and cucumber.